THYROTOXICOSIS SECONDARY TO ALEMTUZUMAB TREATMENT FOR MULTIPLE SCLEROSIS PRESENTING AS PULMONARY HYPERTENSION. Issue 11 (14th October 2015) - Healy, S; Willis, MD; Pickersgill, TP; Page, M; Robertson, NP
Abstract : Alemtuzumab has been approved for use in the treatment of relapsing multiple sclerosis. Despite its proven clinical efficacy acquired autoimmune disease remains a significant risk. In particular thyroid disease is common and robust surveillance mechanisms are required to identify disease at an early stage. We present the case of a 31-year-old female patient who presented with signs consistent with pulmonary hypertension as the presenting feature of thyrotoxicosis. 12-months after the first alemtuzumab treatment course the patient presented to clinic with a 2-week history of exertional dyspnoea, palpitations and headaches. On examination, she had a new pansystolic murmur loudest in the pulmonary area and bilateral pitting oedema to the knees. An echocardiogram demonstrated elevated right ventricular pressure (40 mm Hg) and tricuspid regurgitation consistent with pulmonary hypertension. A CT pulmonary angiogram did not demonstrate evidence of a pulmonary embolus. Thyroid function tests revealed profound thyrotoxicosis (free T4 37.3 pmol/l and TSH <0.02 mU/l), which was thought to be the likely cause. Carbimazole was started but discontinued due to a rash with euthyroidism eventually achieved with radio-iodine. Her symptoms have subsequently resolved. This case highlights the need for neurologists using Alemtuzumab to be vigilant of the varied and sometimes acute presentations of thyroid dysfunction; and the growing repertoire of induced autoimmunity.